2007
DOI: 10.1111/j.1745-7262.2007.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Gossypol inhibits proliferation of endometrioma cells in culture

Abstract: Gossypol invokes a potent toxicity on cultured endometrioma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Indeed, GP has been shown to inhibit cell growth in a dose-dependent manner in various species, including human. The majority of the studies evaluating the toxic effects of GP at the cellular level have been performed on cancer cells, including those of leukaemia [33], prostate cancer [34], breast cancer [35], ovarian cancer [36], carcinoma [37] and other malignancies [38], with the focus of preventing cancer metastasis. As a result, it has been reported that the proliferation of cancer cells is inhibited by GP toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, GP has been shown to inhibit cell growth in a dose-dependent manner in various species, including human. The majority of the studies evaluating the toxic effects of GP at the cellular level have been performed on cancer cells, including those of leukaemia [33], prostate cancer [34], breast cancer [35], ovarian cancer [36], carcinoma [37] and other malignancies [38], with the focus of preventing cancer metastasis. As a result, it has been reported that the proliferation of cancer cells is inhibited by GP toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The active groups of gossypol also contribute to its reactivity and biological activity. Gossypol -for the treatment of leukemia [1], lymphoma [2], colon carcinoma [3,4], breast cancer [5,6], myoma, prostate cancer [7] and other malignant tumors is a promising agent [8][9][10][11][12] and has broad-spectrum antiviral, antitumor, and antifungal activity.…”
Section: Introductionmentioning
confidence: 99%
“…For agricultural application, gossypol ( Kong et al., 2010 ; Krempl et al., 2016 ) is used to control crop diseases and insect pests due to its good insect resistant characteristic and also for the control of rodent damage in the field due to its fertility resistance ( Hahn et al., 1981 ). In pharmaceutics, the antifertile trait of gossypol is made use of in the manufacturing of contraceptives ( Qian and Wang, 1984 ), drugs that inhibit the growth and proliferation of tumor cells ( Badawy et al., 2007 ; Ni et al., 2013 ), and it has obvious effect on the treatment of gynecological diseases ( Hsieh et al., 2020 ). However, the toxicity of gossypol limits its wide application as an important oil and feed raw material.…”
Section: Introductionmentioning
confidence: 99%